2021
DOI: 10.1029/2020wr028620
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Stem Size on Turbulence and Sediment Resuspension Under Unidirectional Flow

Abstract: Aquatic vegetation is widely distributed in intertidal marshes and rivers and can protect shorelines and banks from erosion by reducing currents and by stabilizing the bed (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 54 publications
5
45
0
Order By: Relevance
“…We apply the conversion suggested by Soulsby (1983) based on flow measurements in atmospheric and marine boundary layers: is the dimensionless TKE. Previous studies have shown that the critical TKE for sediment entrainment, t,cr E k , is the same for vegetated and unvegetated channels (Liu et al, 2021;Yang et al, 2016). Based on this, we propose that t,cr E k can be estimated from previously determined critical bed shear stress for bare bed, that is, in dimensionless form,…”
Section: Background and Theorymentioning
confidence: 80%
See 2 more Smart Citations
“…We apply the conversion suggested by Soulsby (1983) based on flow measurements in atmospheric and marine boundary layers: is the dimensionless TKE. Previous studies have shown that the critical TKE for sediment entrainment, t,cr E k , is the same for vegetated and unvegetated channels (Liu et al, 2021;Yang et al, 2016). Based on this, we propose that t,cr E k can be estimated from previously determined critical bed shear stress for bare bed, that is, in dimensionless form,…”
Section: Background and Theorymentioning
confidence: 80%
“…The MPM model (Equation ) was recast in terms of TKE (Equation ), which required a prediction of kt,cr. Previous studies have shown that the threshold for grain motion can be described in terms of TKE and that kt,cr is the same for vegetated and unvegetated channels with the same bed sediment (Liu et al., 2021; Tinoco & Coco, 2018; Yang et al., 2016). Hence, we proposed that the threshold of sediment motion documented for bare beds in terms of θcr can be used to estimate the turbulence threshold, kt,cr*=5.3θcr, using Equation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high rods density was n = 100/m 2 for rods distanced s = 0.10 m, resulting in solid volume fraction of ϕ = 3.14% (Nepf 2012). Such values of ϕ in the range [0.001 ÷ 0.04] can be considered representative of reeds and marsh beds (Liu et al 2021) in a coastal environment.…”
Section: Experimental Setup and Measurement Techniquementioning
confidence: 97%
“…We use the Discrete Element Method‐Lattice Boltzmann Method (DEM‐LBM) simulation data to derive continuum models of sediment transport that apply to a range of flow conditions and sediment characteristics. For simplicity, we will limit our investigation to the bedload sediment transport of mono‐disperse particles without considering vegetation (C. Liu et al., 2021; Vargas‐Luna et al., 2015), external agitation of the turbulence (N. Cheng et al., 2020; Ojha et al., 2019; Sumer et al., 2003), or channel morphology that is known to influence the transport relation, such as bedform patterns (Venditti, 2013; Venditti et al., 2017) or the presence of large (possibly not fully submerged) boulders (Yager et al., 2007).…”
Section: Bedload Transport Of Spherical Grainsmentioning
confidence: 99%